HIV-1 Virological Synapse is not Simply a Copycat of the Immunological Synapse. - Vasiliver-Shamis, G; Dustin, M; Hioe, C (2010)
The virological synapse (VS) is a tight adhesive junction between an HIV-infected cell and an uninfected target cell, across which virus can be efficiently transferred from cell to cell in the absence of cell-cell fusion. The VS has been postulated to resemble, in its morphology, the well-studied immunological synapse (IS). This review article discusses the structural similarities between IS and VS and the shared T cell receptor (TCR) signaling components that are found in the VS. However, the IS and the VS display distinct kinetics in disassembly and intracellular signaling events, possibly leading to different biological outcomes. Hence, HIV-1 exploits molecular components of IS and TCR signaling machinery to trigger unique changes in cellular morphology, migration, and activation that facilitate its transmission and cell-to-cell spread.